1984
DOI: 10.3758/bf03203924
|View full text |Cite
|
Sign up to set email alerts
|

A figural approach to the role of melodic contour in melody recognition

Abstract: These experiments looked at specific components of melodic contour, reversals in pitch, and nonreversals, using a short-term recognition memory paradigm. Listeners found it easier to discriminate between same and different melody pairs if changes occurred at contour reversals. This result was independent of rate of presentation, suggesting that the salience of upper and lower reversals is not attributable to a form of perceptual streaming. These results suggest an analogy between auditory and visual contours. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 43 publications
(57 reference statements)
1
13
0
1
Order By: Relevance
“…Here, contour similarities need to be recognized in various frequency ranges ("transpositions") and across varying degrees of frequency excursion ("tunings"). It has been argued that speech contours and melodic contours have similar perceptual properties (Dyson & Watkins, 1984;Thomassen, 1982). This argument is reinforced by the present findings, that the discrimination of contour differences in both melodic and nonmelodic tone sequences is quantitatively similar, there being no reliable differences in the size of the contour effect across the different tunings.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Here, contour similarities need to be recognized in various frequency ranges ("transpositions") and across varying degrees of frequency excursion ("tunings"). It has been argued that speech contours and melodic contours have similar perceptual properties (Dyson & Watkins, 1984;Thomassen, 1982). This argument is reinforced by the present findings, that the discrimination of contour differences in both melodic and nonmelodic tone sequences is quantitatively similar, there being no reliable differences in the size of the contour effect across the different tunings.…”
Section: Discussionsupporting
confidence: 79%
“…It has been suggested that various aspects of the contour are important for the communication of structure in music. For example, Jones (1981) proposed that reversals in contour might emphasize notes of structural importance, and it has been shown that contour reversals in novel melodies are more perceptually salient than are nonreversals (Dyson & Watkins, 1984). Other authors maintain that contour is an important component in memory for music (Dowling, 1978).…”
mentioning
confidence: 99%
“…Several musical features that are easily perceived by relatively untrained listeners-for example, tonal function (Dowling, 1978) and melodic contour (Dyson & Watkins, 1984;Jones & Ralston, 1991)-failed to emerge as significant predictors of melody identification. This result may reflect the fact that standard music perception paradigms require the listener to detect manipulations of single notes.…”
Section: What Are the Fundamental Units For Melody Identification?mentioning
confidence: 99%
“…A reversal of contour direction refers to a change from a rising pitch line to a falling pitch line, or vice versa. Research has shown that alterations to a previously heard melody are more easily detected when they occur at contour reversals than when they occur at other locations (Dyson & Watkins, 1984). Further, Jones (1987;Jones & Ralston, 1991) has argued that points of contour inflection serve as melodic accents that draw the listeners' attention and have shown that changes in contour direction significantly affect melody perception (Boltz, Marshburn, Jones, & Johnson, 1985;Cuddy et al, 1981;Monahan et al, 1987).…”
Section: Contour Patternsmentioning
confidence: 99%
See 1 more Smart Citation